PEMBUATAN SELAI UBI JALAR UNGU DI DESA HITU, KECAMATAN LEIHITU, KABUPATEN MALUKU TENGAH - C. D. Tuhumury, Helen; Moniharapon, Erynola; Souripet, Agustina (HIRONO : Jurnal Pengabdian Masyarakat, 2022)
This community service activity aimed to improve the community's knowledge and skills in making purple sweet potato jam in Hitu Village, Leihitu District, Central Maluku Regency. This activity's target audience is PKK women in Hitu Village, and the methods employed are extension, demonstration, and training. As evidenced by the participants' enthusiasm for participating in the activity, their level of knowledge about the characteristics and health benefits of purple sweet potatoes increased, and they became skilled at making purple sweet potato jam